Ethnomedicinal Study of the Use of Zingiberaceae by the Mentawai People in Siberut, West Sumatra, Indonesia - Nurainas Nurainas; Ratna Sulekha; Zuhri Syam; Samantha Lee; Syamsuardi Syamsuardi (Jurnal Biologi Universitas Andalas, 2021)
The Mentawai archipelago is situated to the west of mainland Sumatra and is part of the West Sumatra province. The Mentawai people are indigenous to this archipelago and are well known for their traditional healing practices performed by their Sikerei healers. Only a few studies on the traditional plant medicines of the Mentawai people have been published, which mostly suggest that Zingiberaceae is one of the most widely used families. This study examines the indigenous knowledge of Zingiberaceae by the Mentawai people living in Siberut. Field surveys were undertaken at four locations in the island where the Sikerei healers were interviewed directly to obtain information about medicinal treatments using plants from the Zingiberaceae family. Voucher specimens were collected, dried and deposited at the Herbarium of Andalas University (ANDA), Padang, West Sumatra. The study suggests that at least 32 Zingiberaceae species are used in the Mentawai’s traditional medicines. The floristic aspects, the plant part used, and the type of disease treated are discussed.